Fabrication and Characterization of Copper System Compound Semiconductor Solar Cells - Ryosuke Motoyoshi; Takeo Oku; Atsushi Suzuki; Kenji Kikuchi; Shiomi Kikuchi; Balachandran Jeyadevan; Jhon Cuya (Advances in Materials Science and Engineering)
Copper system compound semiconductor solar cells were produced by a spin-coating method, and their cell performance and structures were investigated. Copper indium disulfide- (CIS-) based solar cells with titanium dioxide (TiO2) were produced on F-doped SnO2 (FTO). A device based on an FTO/CIS/TiO2 structure provided better cell performance compared to that based on FTO/TiO2/CIS structure. Cupric oxide- (CuO-) and cuprous oxide- (Cu2O-) based solar cells with fullerene (C60) were also fabricated on FTO and indium tin oxide (ITO). The microstructure and cell performance of the CuO/C60 heterojunction and the Cu2O:C60 bulk heterojunction structure were investigated. The photovoltaic devices based on FTO/CuO/C60 and ITO/Cu2O:C60 structures provided short-circuit current density of 0.015 mAcm−2 and 0.11 mAcm−2, and open-circuit voltage of 0.045 V and 0.17 V under an Air Mass 1.5 illumination, respectively. The microstructures of the active layers were examined by X-ray diffraction and transmission electron microscopy.